BVGer D-4314/2019 vom 17. Juli 2019 - Bundesverwaltungsgericht (2019)
Asyl und Wegweisung (Mehrfachgesuch/Wiedererwägung) | Asyl und Wegweisung (Mehrfachgesuch/Wiedererwägung); Verfügung des SEM vom 17. Juli 2019